Компетенція правоохоронних органів як суб’єктів взаємодії та координації на регіональному рівні на прикладі Національної поліції України та Національної гвардії України - Русецький, А. А.; Rusetskyi, A. A. (Науковий вісник публічного та приватного права. - 2018. - Вип. 6, т. 2. - С. 104-109, 2018)
Розглянуто питання компетенції правоохоронних органів як суб’єктів взаємодії та координації на регіональному рівні на прикладі Національної поліції України та Національної гвардії України. Під компетенцією пропонується розуміти сукупність прав та обов’язків, які закріплюються нормами чинного законодавства за кожним правоохоронним органом із метою виконання завдань і функцій, встановлених державою. Зазначено, що в рамках компетенції кожного правоохоронного органу передбачено низку повноважень, що забезпечують взаємодію між ними як на центральному рівні, так і на рівні регіонів. Крім того, обсяги компетенції правоохоронних органів, що діють на рівні регіонів, є більш динамічними, оскільки безпосередньо спрямовані на реалізацію правоохоронної функції держави та оперативне вирішення завдань.

In the article, based on the analysis of the norms of the current legislation of Ukraine, the issue of competence of law enforcement bodies as subjects of interaction and coordination at the regional level, on the example of the National Police of Ukraine and the National Guard of Ukraine was considered. It is emphasized that the tasks and functions of law enforcement bodies should be carried out exclusively within the limits of their competence and authority, that is, competence and powers are within the framework within which the law-enforcement body operates. It is stressed that, if this framework is violated, we will result in either abuse of our rights or interference in the activities of other structural units of state authorities. Therefore, it is the competence and powers, together with the above-stated tasks and functions of the law-enforcement bodies, provide a coherent picture of the meaning and essence of their activities. Under the jurisdiction, it is proposed to understand the set of rights and obligations, which are fixed by the rules of the current legislation for each law enforcement agency in order to fulfill the tasks and functions established by the state. It is noted that competence is the basis of the legal status of each law enforcement agency, which makes it possible, first, to distinguish them from each other, and secondly, to trace the algorithm of action and the direction of each of them, and make sure that they are aimed at the realization of tasks and state functions. It is noted that within the competence of each law-enforcement agency there are a number of powers that ensure interaction between them both at the central level and at the regional level. In addition, it is noted that the scope of competence of law enforcement bodies operating at the regional level is more dynamic, since they are directly aimed at the implementation of the law enforcement function of the state and the operational resolution of tasks.

Рассмотрены вопросы компетенции правоохранительных органов как субъектов взаимодействия и координации на региональном уровне на примере Национальной полиции Украины и Национальной гвардии Украины. Отмечено, что в рамках компетенции каждого правоохранительного органа предусмотрен ряд полномочий, которые обеспечивают взаимодействие между ними как на центральном уровне, так и на уровне регионов. Кроме того, объемы компетенции правоохранительных органов, действующих на уровне регионов, более динамичны, поскольку непосредственно направлены на реализацию правоохранительной функции государства и оперативное решение задач.
Русецький, А. А. Компетенція правоохоронних органів як суб’єктів взаємодії та координації на регіональному рівні на прикладі Національної поліції України та Національної гвардії України / Русецький А. А. // Науковий вісник публічного та приватного права. - 2018. - Вип. 6, т. 2. - С. 104-109.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; National police of Ukraine; Национальная полиция Украины; поліція; police; полиция; Національна гвардія України; National Guard of Ukraine; Национальная гвардия Украины; компетенція; competence; компетенция; правоохоронні органи; law enforcement agencies; правоохранительные органы; взаємодія; interaction; взаимодействие; координація; coordination; координация